Strategi Manajemen Sumber Daya Insani BPRS Lantabur Tebuireng Jombang dalam Menangkal Praktik Rentenir di Pasar Tradisional - Achmad Arfinanto Arsyadani; Aji Damanuri (Indo Publishing, 2025)
The practice of money lending in traditional markets remains a serious issue that burdens small traders and increases economic inequality. As an alternative, Islamic financial institutions based in pesantren such as BPRS Lantabur Tebuireng Jombang provide fair, transparent, and empowering financial services for micro communities. This study aims to analyze the human resource management strategies implemented by the institution in supporting Islamic financial inclusion and reducing dependence on moneylenders. The research uses a qualitative method with a case study approach through in-depth interviews, participatory observation, and documentation. The findings show that comprehensive human resource management which includes recruitment, training, moral and spiritual development, as well as employee welfare and occupational safety, enhances staff competence, loyalty, and productivity. This strategy is supported by outreach services, digital transaction development, and Islamic financial literacy programs for market traders, positioning the institution as an agent of economic empowerment and a practical model of pesantren-based Islamic economic development.